2016
DOI: 10.1002/ppul.23483
|View full text |Cite
|
Sign up to set email alerts
|

Lung clearance index and moment ratios at different cut-off values in infant multiple-breath washout measurements

Abstract: In infants, the diagnostic performance of MBW strongly depends on the point of analysis. The cut-off with the highest discriminative power to detect ventilation inhomogeneity in infants with cystic fibrosis and after preterm birth was at 1.5% tracer gas concentration. Pediatr Pulmonol. 2016;51:1373-1381. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…LCI is defined as a number of times lung turn overs (as represented by FRC) have to turn over to the clear the lungs from nitrogen (N 2 ). LCI (LCI 2.5 ) reflects N 2 washout until 1/40 th of the starting N 2 end-tidal concentration (cet), i.e., 2.5% and LCI 5 reflects N 2 washout until 1/20 th of the starting N 2 concentration (Cet), i.e., 5% [49][50][51][52][53]. So, the sicker the child is, the more air it must breathe to clear its lungs from the tracer gas.…”
Section: Introductionmentioning
confidence: 99%
“…LCI is defined as a number of times lung turn overs (as represented by FRC) have to turn over to the clear the lungs from nitrogen (N 2 ). LCI (LCI 2.5 ) reflects N 2 washout until 1/40 th of the starting N 2 end-tidal concentration (cet), i.e., 2.5% and LCI 5 reflects N 2 washout until 1/20 th of the starting N 2 concentration (Cet), i.e., 5% [49][50][51][52][53]. So, the sicker the child is, the more air it must breathe to clear its lungs from the tracer gas.…”
Section: Introductionmentioning
confidence: 99%
“…While potentially sufficient for the clinical setting in preschool children, monitoring early changes in infants or comparison of treatment efficacy may require longer washouts and more sensitive endpoints. Egger et al found that the diagnostic performance of MBW outcomes depends on the analysis cutoff point. In infants with mild lung disease, a longer washout is necessary to discriminate between health and disease, especially since newborn screened infants with CF have minimal ventilation inhomogeneity that is only slightly elevated compared with HC .…”
Section: Discussionmentioning
confidence: 99%
“…Egger et al found that the diagnostic performance of MBW outcomes depends on the analysis cutoff point. In infants with mild lung disease, a longer washout is necessary to discriminate between health and disease, especially since newborn screened infants with CF have minimal ventilation inhomogeneity that is only slightly elevated compared with HC . Although LCI 5 has advantages to LCI 2.5 in young children, and provides a suitable alternative for monitoring lung function in clinical practice, these data support LCI 2.5 as a quantitatively superior outcome in preschool children and may be the preferred outcome for interventional studies for which sensitivity and precision outweigh time savings and feasibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2.5% of the starting tracer gas concentration) in SF 6 washouts for both LCI and moment ratios in infancy. They found optimal discriminative power for moment ratios and LCI to detect differences between healthy controls and infants with cystic fibrosis at 1.5% tracer gas concentration [39].…”
Section: Mbw Indices Other Than Lcimentioning
confidence: 99%